Hysterotomy for Early Placenta Percreta at 10 Weeks Gestation: A Case Report - El-Said N; Kotb AM (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Placenta percreta in early pregnancy is rare and only few cases are documented. We report a case of placenta percreta at 10 weeks gestation. Sonography revealed absence of line of demarcation between trophoblast and myometrium extending to the urinary bladder region. Termination of pregnancy by hysterotomy was done. The diagnosis and treatment of placenta accreta in early pregnancy must be taken seriously which might protect patients from considerable bleeding and further morbidity